Hemagglutination activities of group B, C, D, and G streptococci: demonstration of novel sugar-specific cell-binding activities in Streptococcus suis. - Kurl, D N (1989)
A total of 378 streptococcal isolates of Lancefield groups B, C, D and G were tested for their ability to hemagglutinate untreated, sialidase-treated, and endo-beta-galactosidase-treated human erythrocytes. Of the 43 strains showing positive hemagglutination, 9 were inhibitable with neutral monosaccharides. Four strains were inhibited with galactose and N-acetylgalactosamine, whereas five were inhibited with galactose only. A third, sialic acid-specific adhesion activity was suggested for two additional strains on the basis of their agglutination of native and endo-beta-galactosidase-treated but not sialidase-treated erythrocytes. All the sugar-specific agglutination activities detected were confined to Streptococcus suis strains of group D streptococci, whereas streptococci of other groups did not exhibit these types of hemagglutination activities. The adhesins were sensitive to proteases and heat treatment, which indicates that they were proteins. The hemagglutinating isolates of S. suis originated from pig brain and lung, human brain, and the tonsils of healthy pigs. No clear correlation with a particular serotype was observed. These results demonstrate the occurrence of unique sugar-specific adherence activities in S. suis, an important pig pathogen with occasional human pathogenicity.